ANALISIS PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN DENGAN SELF ESTEEM SEBAGAI VARIABEL INTERVENING (Studi Pada Perusahaan Perkebunan di Provinsi Bengkulu) - Aan Shar; Herry Novrianda (Management Insight: Jurnal Ilmiah Manajemen, 2017)
The objective of this research is to test the effect of compensation toward employee performance with self esteem as intervening variable. This study is a descriptive research which aims to clarify the relationship or influence that exist between the variables studied. The type of data used a primary data that is collected from questionnaires. Respondents of this study is the employees of plantation company in Bengkulu Province as many 196 people were taken with the judgemental (purposive sampling) technique. The methods of data analysis used are descriptive analysis by using the mean, frequency distribution table and regression analysis. The based on result of analysis, obtained result that: 1). Compensation has a positive and significant effect on the employee's self esteem. This means that the higher the employee's compensation, the employee self esteem will also be higher; 2). Compensation has a positive and significant effect on employee performance. This means that the higher the employee's compensation the employee's performance will also be better; 3). Self esteem has a positive and significant effect on employee performance. This means that the higher the self esteem of an employee the employee performance is also better; And 4). Compensation affects employee performance with self esteem as intervening variable, but direct influence is greater than indirect influence. This means that self esteem serves only as a partial mediation variable only.Keywords: compensation, performance, self esteem.